Evaluation of the Anti-inflammatory Effect of Intra-articular Injection of Chondroitin Sulfate and Sodium Hyaluronate in Mechanically Induced Temporomandibular Joint Injury in Rabbits - Elsayed, Lubna K.; Elsharrawy, Eman; Elsholkamy, Mohammed; Tawfik, Mona K. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Degenerative arthritis is the most common form of arthritis, usually affecting the hands, feet, spine, knees, and temporomandibular joint (TMJ) as well. TMJ degenerative arthritis causes symptoms of painful joints, loss of joint function, limited mouth opening, joint instability, and clicking. Non-surgical symptomatic treatments can successfully be used to treat patients with degenerative arthritis. AIM: This study aimed to evaluate the anti-inflammatory effect of intra-articular injection of chondroitin sulfate and sodium hyaluronate in mechanically induced acute injury in TMJ of rabbits. METHODS: An animal study was conducted, all rabbits received a mechanical injury using a contra-angle handpiece with a speed of 120 rpm of a fissure bur 4 mm in diameter and 4 mm in depth extending to subchondral bone. Thirty-two rabbits were randomized into four groups: Control group, sodium hyaluronate “SH” group, chondroitin sulfate “CS” group, and “CS-SH” group. After 7 days, rabbits in the control group, “SH” group, “CS” group, and “CS-SH” group were respectively treated with normal saline, sodium hyaluronate, chondroitin sulfate, or combination of CS&SH injection in the TMJ. All animals were treated once weekly for 3 weeks. A histological evaluation was performed. RESULTS: Histological findings showed a significantly reduced inflammatory cell, bone resorption, and fibrosis in the CS-HA-treated group. CONCLUSION: CS-SH injection has an anti-inflammatory effect on TMJ degenerative arthritis and aids in the reparative process.